2011
DOI: 10.1158/1535-7163.mct-10-0985
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Suppresses Androgen Receptor Signaling in Prostate Cancer

Abstract: The androgen receptor (AR) is critical in the normal development and function of the prostate, as well as in prostate carcinogenesis. Androgen deprivation therapy is the mainstay in the treatment of advanced prostate cancer, however, after an initial response, the disease inevitably progresses to castration-resistant prostate cancer (CRPC). Recent evidence suggests that continued AR activation, sometimes in a ligand-independent manner, is commonly associated with the development of CRPC. Thus, novel agents tar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 45 publications
3
76
0
2
Order By: Relevance
“…BBR as an isoquinoline derivative alkaloid has been demonstrated to have diverse pharmacological activities involving multiple biological mechanisms, which may be utilized for the treatment of a wide variety of diseases (9)(10)(11)(12)(13)(14). Previous studies have demonstrated that BBR acts as an LPS antagonist and blocks LPS/TLR4 signaling in an LPS-induced animal model (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BBR as an isoquinoline derivative alkaloid has been demonstrated to have diverse pharmacological activities involving multiple biological mechanisms, which may be utilized for the treatment of a wide variety of diseases (9)(10)(11)(12)(13)(14). Previous studies have demonstrated that BBR acts as an LPS antagonist and blocks LPS/TLR4 signaling in an LPS-induced animal model (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that BBR possesses different pharmacological activities involving multiple biological mechanisms, and may be utilized for the treatment of various diseases, including diabetes, metabolic syndrome and various types of cancer (9)(10)(11)(12)(13)(14). It was reported that BBR has a beneficial effect on patients with diabetes and obesity, partly by stimulating adenosine monophosphate kinase activity (15).…”
Section: Introductionmentioning
confidence: 99%
“…Berberine can induce apoptosis in a variety of cancer cells (12,13,(18)(19)(20). We, therefore, determined whether berberine could also induce apoptosis of glioblastoma cells.…”
Section: Berberine Induces Cellular Senescence Of Glioblastoma Cellsmentioning
confidence: 99%
“…It is shown to possess anticancer activities against various types of cancer cells. Berberine can induce apoptosis and cell-cycle arrest of tumor cells (10)(11)(12)(13)(14). In this report, we studied the effect of berberine on glioblastoma cells in vitro and on tumor xenografts.…”
Section: Introductionmentioning
confidence: 99%
“…Recent pharmacological studies of berberine have demonstrated that this molecule alleviates diabetic nephropathy (13), rheumatoid arthritis (14), and inflammation (15). Moreover, berberine has antioxidant effects (16,17), prevents obesity (18), and has anticancer activities in breast (19), prostate (20), cervical (21), gastric (22), oral (23,24), and ovarian cancers (25). Although these anticancer effects of berberine and associated cell signaling pathways have been reported in various cancers, the effects of berberine on apoptosis have not been reported in HNSCC.…”
Section: Berberine-induced Anticancer Activities In Fadu Headmentioning
confidence: 99%